Oligonucleotide based therapeutic strategies for tackling schizophrenia - A systematic review - Jabir PK,; Cheriyan, Sumina; Korath, Pooja; Sai Sailesh Kumar Goothy, (Asian Journal of Medical Sciences, 2023)
Schizophrenia is a serious mental disorder that affects the quality of life of patients, and the cure for the disease is yet a mirage. Drugs are having side effects and not giving satisfying results. Recently, genes have been isolated. The role of oligonucleotide in many diseases, such as multiple sclerosis and cancer, is promising. Since oligonucleotides can modulate gene expression, these molecules can be used as drugs in several conditions which are beyond the usage of conventional drugs. They are also important in the future as therapeutic drugs like rare diseases, which are genetic and in which specific sequences of genes are to be addressed. Since they can bind to Cas9 protein, they can be used for gene editing. Even though the delivery of oligonucleotides faces some limitations, they can be delivered to targets using chemical modification, bioconjugation, and nanotechnology. Overall, they can be used in research, diagnosis, and therapy. Since they are small in size, they have target affinity. They are also cheap to synthesize and more stable than antibodies. This review summarizes the pathophysiology of schizophrenia and its current treatment, recent updates, and insights into the role of oligonucleotide and its regulation of genes. In this article, we also reviewed the genetics of schizophrenia and the possible application of oligonucleotides in the therapeutics of schizophrenia. The introduction of oligonucleotides in the therapy of schizophrenia can be a possible strategy that can be put forward in the future for the management of schizophrenia.